LITERASI DIGITAL MARKETING BAGI UMKM DESA WARINGINJAYA - Muhammad Fajar Oktara; Muchammad Al-Fatih; Devi Amalia; Eka Nurfaidah; Purwanti Purwanti (Jurnal Padamu Negeri, 2025)
Community Service Program (KKN) is a concrete manifestation of the Tri Dharma of Higher Education, which aims to encourage students to participate directly in community development. The KKN activity, held in Waringinjaya Village, Kedungwaringin District, Bekasi Regency, carried the theme "Synergy to Create Inclusive, Competitive, and Independent Villages in Supporting Sustainable Development." The main focus of this activity is to improve digital marketing understanding for Micro, Small, and Medium Enterprises (MSMEs) through blended learning that combines face-to-face and online training with intensive mentoring. The method used is Participatory Action Research (PAR) with activities such as the use of social media (Instagram, Facebook, WhatsApp), digital content creation, use of QRIS for payments, and management of online business accounts. Evaluation was carried out through observation, questionnaires, interviews, and sales case studies. The results of the implementation showed a significant increase in digital literacy and online marketing skills of the participants. In addition, the program also had a positive impact in the form of market expansion, increased brand awareness, and increased sales volume of local products.